REFLECTING ON THE LESSON CONDUCTED AT THE STATE UNIVERSITY - Arslonbekova, Rano (Innovative Development in Educational Activities, 2024)
In this article I will talk about my lesson I have conducted with a group of junior students in a public university. The students’ level of the English language is early intermediate. The language of instruction is English, but Russian and Uzbek is also used to explain words or expressions difficult to interpret. Some steps of successful lesson were described and some recommendations were given.